Use of The Merdeka Teaching Platform Application In The Implementation of the Independent Curriculum - Alawiah, Enok Tuti; Setyorin, Dini (IJISTECH (International Journal of Information System and Technology), 2023)
Independent Teaching Platform is an application launched by the Ministry of Education, Culture, Research and Technology aimed at teachers in the framework of adaptation to the independent curriculum. This application must be used by teachers to share information, good practices, aspiration videos and learning resources. The Merdeka Mengajar Platform is an application launched by the Ministry of Education, Culture, Research and Technology aimed at teachers in the framework of adaptation to the independent curriculum. This application must be used by teachers to share information, good practices, aspiration videos and learning resources. However, the Merdeka Mengajar Platform has not been fully accepted by teachers because not all teachers have the ability to access information technology, inadequate infrastructure, difficulty accessing and lack of motivation in learning the new paradigm so that they enter into using the old paradigm in the learning process in class. This study uses the TOPSIS method, which is a multi-criteria method used to find the most ideal preference value in the decision-making process. The results of the study obtained a score of 8.35 for the Readiness of the Education Unit, which means that the use of the Merdeka Mengajar Platform in its implementation requires the readiness of the Education unit which consists of the Principal, Learning Committee and Teachers